BETSEE: testing for system-wide effects of single event effects on ITk strip modules. (1st January 2023) - Belanger-Champagne, C.; Dandoy, J.; Gallop, B.J.; Gosart, T.C.; Helling, C.M.; Keener, P.; Krizka, K.; McGovern, B.; Mullier, G.; Poley, A.-L.; Roberts, B.R.; Sawyer, C.; et al.
Abstract: The Inner Tracker silicon strip detector (ITk Strip) is a part of the ATLAS upgrade for the HL-LHC. The detector readout and control is accomplished by the interaction of three on-module custom ASICs (ABCStarv1, HCCStarv1 and AMACstar). All ASICs are designed with protections against Single Event Errors. Their resilience at the system-level can be tested using the Board for Evaluation of Triple-chip Single Event Effects (BETSEE). This special board places all three ASICs into the beam-spot of a test beam facility concurrently and allows for module-like operation. The results from irradiating BETSEE with heavy ions and protons will be presented.